Korea and Australia’s P&MA Shift: From Local Launch Opportunities to Regional Blueprint. - Siow, Joshua; Chang, Lauren (Pharmaceutical Executive, 2025)
The article focuses on recent policy shifts in Korea and Australia that are transforming their pharmaceutical pricing and market access (P&MA) landscapes, making them more favorable for innovative therapies. Both countries are implementing reforms aimed at expediting access to new drugs, with Korea introducing parallel processing for regulatory approval and reimbursement, and Australia enhancing its commitment to rare diseases and innovative financing models. These changes not only promise faster and more efficient market entry for pharmaceutical companies but also position Korea and Australia as potential regional leaders in health technology assessment (HTA) practices within the Asia-Pacific (APAC) region. The article highlights the strategic implications of these reforms, suggesting that other APAC markets may adopt similar approaches to improve access to innovative treatments.